Low-cost synthetic model for skin flap training - Arthur Antunes Coimbra Pinheiro Pacífico; Aline Santos Correia; Bárbara Matos de Carvalho Borges; Mateus Bonfim Costa; Mateus Pinheiro Fernandes Feitosa Arrais; Samy Lima Carneiro; Thiago Maciel Valente; Nelson Gurgel Simas de Oliveira (Revista Brasileira de Cirurgia Plástica)
Introduction: The search for learning surgical techniques within the operating room is linked to difficulties, such as reducing teaching time by surgeons and ethical problems. Models have already been developed to facilitate the practice of surgical techniques, however, with high cost, difficult access, and ethical and moral complications. The present work aims to present a synthetic model, unpublished and practical for the training of skin flap techniques, formulated to be easy to reproduce and low cost, allowing its feasibility. Methods: In the model, fabric, sponge for car washing, latex elastic, fine-tipped brush, scalpel, and surgical suture instruments were used. The fabric is fixed by the elastic on the surface of the sponge, simulating skin and subcutaneous. The flap to be made on the surface of the fabric is then drawn. Results: The model created was satisfactory, since it improves the handling of surgical instruments and the learning of the proposed flap technique, besides having demonstrated good elasticity and tensile strength. In medical schools, there is a lack of approach to essential topics in plastic surgery. The importance of low-cost and easy-to-execute models, such as the above, is emphasized to facilitate the learning of students interested in the subject, seeking to fulfill the educational function without breaking ethical principles. Conclusion: The proposed model is an excellent form of training because it presents logistical and instructive benefits, facilitating learning, without causing harm to animals.